Runninghot! 2010 - Bostock, Helen; Crampin, Edmund; Shaw, Richard; Parker, Emily (New Zealand Science Review, 2011)
Runninghot! 2010 was the third in the Runninghot! Series of conferences organised jointly by He Waka Tāngata and the Oxygen Group and supported by the Ministry for Research Science and Technology (MoRST). The conference built on the momentum established by the 2006 and 2008 events, and focused on realising the value of research for New Zealand. The conference agenda addressed the different forms of value that can be derived from current research, and to identify practical ways of enhancing and realising the benefits of future research in New Zealand.